Report on the IIT (BHU) Varanasi Student Branch Chapter Activities for 2022 [MTT-S Society News] - Bhattacharyya S. (My University, 2025)
Provides society information that may include news, reviews or technical notes that should be of interest to practitioners and researchers. © 2000-2012 IEEE.